بنه‌ما جوگرافیه‌ ئابورییه‌كانی‌ په‌ره‌پێدانی پیشه‌سازییه‌ كشتوكاڵیه‌كان له‌ پارێزگای سلێمانی (2009 – 2021) - تالب, جه‌زا تۆفیق; حمه‌یوسف, عطا حمه‌لاو (Sulaimani Journal for Humanities, 2023)
Agricultural industries are considered to be one of the most important types of industrial activities in Sulaimani province. The reason for this importance is that the country relies on local agricultural raw materials for the production of food and non-food industrial products. The increase in the number of residents and the increase in their quality of life has caused an increase in the demand for these kinds of projects, which has had a direct impact on the establishment and development of these industries. From this perspective, this study shows that the economic principles available in the province play a role in the development of agricultural industries, the most important of these principles are raw materials, market, transportation, energy, and capital. The study found that the population in slemani along with their high-income rates has impacted the production from these industries, having more demand for it as opposed to other governorate in Kurdistan and Iraq. Moreover, the production in the agricultural industry has been leaning towards food production rather than non-food products due to the lack of raw materials.